Nature Inc. : environmental conservation in the neoliberal age - Büscher, Bram, 1977-; Dressler, Wolfram Heinz; Fletcher, Robert, 1973- (Critical green engagements., 2014)
""Nature Inc. brings together cutting-edge research by respected scholars from around the world to analyze how 'neoliberal conservation' is reshaping human-nature relations"--Provided by publisher"--